(untitled) (Psychology Travelogs, 2022)
The relevance of a person-oriented approach in education is growing as the next step in the process of improvement and establishing a balance between education and the requirements of today. Society expects a high level of creativity, independence and logical thinking, tolerance, empathy and the formation of such key competencies as social, communicative, instrumental, research, and informational from a modern primary school teacher. The above gave birth to changes in education, changing the vector of its goals and combining not only the training of a professional, competitive teacher, who is in demand on the education market, but also a competent person who is ready to quickly make the right decision in various situations, practically apply the knowledge gained and effectively interact with by others.